Hourly simulations of an hospital building for assessing the thermal demand and the best retrofit strategies for consumption reduction. (June 2018) - Silenzi, Federico; Priarone, Antonella; Fossa, Marco
Highlights: Methodology to optimize the selection for retrofit interventions of buildings Dynamic simulations with Energy Plus are used. Key point index definition and comparisons among different test cases. Intervention Package selection and economic assessment of best solutions. Economics of "intervention packages" are assessed with simple payback period. Abstract: In the framework of energy saving and environmental protection, the role of the energy consumption in buildings is crucial. For existing buildings and especially for public ones, it is mandatory to correctly select and realize suitable retrofitting interventions to reduce costs and increase the efficiency. In fact, innovative solutions for both the envelope and the plants renovation are often very expensive and the correct choice becomes critical for the sustainability from the economic point of view. The aim of the present paper is to propose a methodology to optimize the process of selection for the retrofit interventions, here applied to a case study of the Monoblocco Pavilion at the San Martino Hospital in Genova, Italy. The building thermal behaviour is dynamically simulated by means of an Energy Plus model in order to evaluate the energy needs for both heating and cooling purposes. The base case scenario is evaluated in terms of key performance indicators (KPIs) and compared with benchmark values in order to select the more suitable intervention actions. For the analysed case study, the innovative retrofit solutions are façade void insulated panels, smart rotating windows with different emissivity glass and sunlight carrying optical-fibres coupled with dimmed LED lighting system. The technologies are combined in different intervention packages that are then compared in term of energy saving and economic sustainability by means of the estimation of hourly values of energy consumption and the assessment of the Simply Pay Back Period (SPB) of the investment.